Building the Test of Drawing Skill for the Female students of Kindergartens' Department (Journal of the College of Education for Women, 2019)
The research issue and its importance concentrate on the importance of choosing andpreparing the kindergarten's teacher educationally ,psychologically and artistically ,and otheraspects because of their need for several skills such as the drawing skill for kindergartencurriculums include a various artistic experiences and activities as well as for the drawingimportance for the child .And from this, the research goals raise from to prepare a test thatmeasures the drawing skill for kindergarten students and measure the drawing skill in all fourkindergarten students at the kindergarten department and recognize the differences level forthese students . In order to achieve the first goal in the research ,the researchers builds a testfor drawing skill in accordance with the artistic expression activities in kindergarten .And thetruth and the analytic statistician ( recognition ,the relationship of item degree with the totaldegree ,the difficulty parameter and stability) so a sample construction amounted (300)female students from kindergartens' department\University of Bagdad\College of educationfor girls and Mustansiriya University College of basic education, and then had beencalculated and applied on a sample of (100) female student in kindergarten students .Theresults showed that the degree of drawing skill level was medium in female students ,and thethird stage students were better than other stages in drawing skill .Thereby ,the test appears inits final form which includes : the drawing skill test , human shape ,cat ,palm tree ,and car,during a specific time (13) minute, while the correction standard was as follows:1. Each sub-skills in less than specific time given degree (1)2. Sub skills less in time or less or more than the specified time given degree (zero)